Perancangan Aplikasi Kasir Berbasis Website Menggunakan Barcode Reader Pada Toko Mulia Pancing - Dini Vita Aspuri; Saputra, Herlambang; Azro, Isnainy (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
Toko Mulia Pancing is a small and medium business that provides a wide selection of goods and tools for fishing. Financial management processes such as recording transactions and processing stock data are still done manually so errors often occur. This website, named "Kasir muliaPancing", aims to overcome this problem by providing a barcode scanning feature, storing sales report data and stock reports. The system was built using the PHP programming language with the CodeIgniter Framework and MySQL database. The results of this research are a website that can only be accessed at two levels, namely admin as owner and user as cashier. On the website there is a menu to store supplier, customer, product, transaction, invoice, and report data. Where each menu has its own function which aims to make it easier for users to make transactions. Website testing uses the black box testing method which produces output as expected   Keywords— Cashier, Website, Barcode Reader, Mulia Pancing Shop